The Environmental Security and International Relations: The Case of Citarum River Water Pollution - Djelantik, Sukawarsini (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2025)
Environmental security as part of human security is a very significant global issue. Environment security became the concern of the Sustainable Development Goals (SDGs) achievement, namely securing the source of ground water which is an important problem in developing countries. This paper analyses the Citarum River, the longest river in West Java, Indonesia, which is heavily polluted due to various economic activities along the riverbanks. The process of industrialization, development and demands to meet the needs of life, as well as population growth have not succeeded in maintaining the river as a source of life. Economic interests and various political conflicts were unable to maintain environmental sustainability. The river pollution comes from factory waste operating along the river, without a process through the Wastewater Treatment Plant (WTP). The research would focus on the government securitization programs in Citarum River, by implementing four components of securitization namely referent objects, scope, mean, and actors. The analysis observed various government efforts and private sectors to restore the river. The research started in 2000, which is the beginning of “Citarum Harum” restoration until the end of the program in January 2025. The research found that securitisation efforts failed due to three issues; the corruption, collusion and nepotism (CCN) issues, lack of law enforcement, and weakness of bureaucracy and leadership. As a conclusion, various securitisation efforts need to be carried out more firmly and earnestly by providing adequate legal sanctions for the perpetrators of environmental damage. Keywords: security, environment security, Citarum River, restoration